Bullying Prevention Method in High School with Humanistic-Religious Approach - Suratno Suratno; Wantini Wantini; Suyatno Suyatno; Djamaluddin Perawironegoro; Mhd Lailan Arqam (Journal of Social Science, 2022)
Bullying has an impact on victims, not only in a short time, but in a long time. Victims usually experience various symptoms such as anxiety, depression, pain due to blows, and so on which require a relatively long time to heal. Victims of bullying also become perpetrators of future bullying because of revenge for what they have experienced. Therefore, counseling guidance has an important role in preventing bullying in high school. The purpose of this study is to analyze the model of preventing bullying cases so that they do not occur in school institutions. In this study, the author uses a descriptive method with library research. Based on the results of the study, it was found that preventing bullying behavior with a religious humanistic approach can be done by: Coping strategies, habituation, guidance, coordination with parents, affection and example, in order to provide students with an understanding of the impact that occurs after bullying.